Dietary intake in healthy older individuals is associated with lipopolysaccharide binding protein a biomarker of gut function: an exploratory cross-sectional study - Jones, Debra; Morrison, Douglas J.; Gray, Stuart R.; Ozanne, Susan E.; Celis-Morales, Carlos; Jain, Mahek; Mattin, Lewis R.; Gittins, Matthew; Alkhedhairi, Saleh A. A.; Dorling, James L.; Burden, Sorrel (Frontiers in Aging, 2025)
Diet, physical function and gut health are important modifiable factors in ageing. However, it is unclear how ageing affects various domains of gut function. Aims of this cross-sectional study were to explore relationships between nutrient intake, physical function, and biomarkers of gut function in older individuals. Healthy participants (n = 94, mean age 71.1 years SD 5.10, 56% female) were recruited to investigate the relationship between nutrient intake (protein, fibre, carbohydrate, fat), physical function (chair rise time, handgrip strength) and lipopolysaccharide (LPS) binding protein (LBP); a marker of gut permeability. Linear regression models, adjusted for age, fat mass/fat free mass ratio, weight and gender, reported LBP changed by; −161.9 ng/mL (95% CI -323.0, −0.8) for every 1 g increase in daily fibre/1,000 kilocalories; 80.5 ng/mL (6.7, 154.2) for 1% increase in daily energy intake as fat; and −88.1 ng/mL (−146.7, −29.6) for 1% increase in daily energy as carbohydrates. When further adjusted for C-reactive protein (CRP), a marker of inflammation, LBP decreased by an additional 6.9 ng/mL for fibre, increased by an additional 4.0 ng/mL for fat and decreased by an additional 3.7 ng/mL for carbohydrate. These findings suggest that in healthy older adults’ nutrient intake is associated with LBP, and CRP appears to slightly modify these associations. There were no associations between LBP and handgrip strength or chair rise time. Results suggest that fibre, fat, and carbohydrates are important for maintaining gut function, potentially mediated by inflammation in older adults, although further research is needed to explore the implications for physical function and CRP as a mediator.